2021
DOI: 10.3389/fpls.2021.765077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutrient Addition on the Productivity and Species Richness of Grassland Along With an Elevational Gradient in Tajikistan

Abstract: Grasslands provide key resource for the millions of people who are dependent on livestock in Tajikistan. Productivity and species richness (SR) are important characteristics of grassland ecosystems and are greatly affected by nutrient inputs. The effect that climate change might have on these characteristics remains unclear. Here, an in situ nitrogen (N) and phosphorus (P) fertilization experiment was conducted at four sites along with an elevational gradient (650, 1,100, 1,250, and 2,000 m) in western Tajikis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The major differences between the negative biomass-diversity results obtained in this study and the other widely detected relationships could be linked to nutrient levels and light competition ( Zhou et al., 2016 ; Li et al., 2017 ; Fayiah et al., 2019 ). In mountainous areas, climate factors also regulate plant growth ( Fan et al., 2021 ). In this study, the AGB of the dominant species fluctuated among the years with the highest values occurring in 2022 when the diversity index values were lowest ( Figures 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major differences between the negative biomass-diversity results obtained in this study and the other widely detected relationships could be linked to nutrient levels and light competition ( Zhou et al., 2016 ; Li et al., 2017 ; Fayiah et al., 2019 ). In mountainous areas, climate factors also regulate plant growth ( Fan et al., 2021 ). In this study, the AGB of the dominant species fluctuated among the years with the highest values occurring in 2022 when the diversity index values were lowest ( Figures 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may have been because P. pabularia occupied more habitat space and resources in the well-resourced environments, leading to an increase in its biomass and biomass suppression in other species, which would reduce diversity. Combining the diversity analysis with precipitation and temperature showed that precipitation and temperature in 2022 were suitable for plant growth ( Fan et al., 2021 ; Figures 1 , 2 ). As a result, an increase in the AGB of the dominant species decreased species diversity ( Stevens et al., 2004 ; Koerner et al., 2018 ) through light competition ( Hautier et al., 2009 ; DeMalach and Kadmon, 2017 ), which caused a negative biomass-diversity relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant growth and primary productivity are known to be stimulated by increased precipitation amounts, as supported by various studies (Robertson et al, 2009;Bao et al, 2020;Cheng et al, 2021;Fan et al, 2021). However, the water requirements of plants vary during different developmental stages (Gutierrez et al, 2010;Alam et al, 2021;Sun H. et al, 2021), with higher water requirements in the early growing season than in the late growing season for optimal growth (Sun R. et al, 2021).…”
Section: Introductionmentioning
confidence: 95%